2017
DOI: 10.18639/rabm.2017.03.509325
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Sleep Disorders among HIV Out-Patients in a Tertiary Hospital

Abstract: Human immunodeficiency virus (HIV)-infected individuals have been shown to have a high prevalence of sleep disturbances. Both the effects of the virus and the antiretroviral drugs may cause sleep disturbances. We sought to determine the prevalence and predictors of sleep disorders among HIV seropositive adult subjects presenting at an outpatient hospital setting. One hundred and fifty six subjects were recruited for the study by using a sleep disorder screening questionnaire. The mean ages of the participants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
7
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 23 publications
7
7
2
Order By: Relevance
“…However, the prevalence in the current study was lower than the study conducted in Nigeria which is 59.3% [17]. The finding in the current study was higher than the result reported from South Africa which showed that the prevalence of poor sleep quality was 52% [27], 46.2% in University of Calabar teaching Hospital, South Nigeria [28], Iran 47.5% [29], China 43.1% [30], Brazil 46.7% [31], France 47% [21], Southern US 40% [32], John Hopkins Medical Institution USA 56% [33], another study in USA 46.1% [16] and Taiwan 27.4% [34]. These discrepancies might be due to various factors including differences in the geographical area, socio-cultural variation, characteristics of study participants and the inclusion and exclusion criteria used.…”
Section: Discussioncontrasting
confidence: 76%
“…However, the prevalence in the current study was lower than the study conducted in Nigeria which is 59.3% [17]. The finding in the current study was higher than the result reported from South Africa which showed that the prevalence of poor sleep quality was 52% [27], 46.2% in University of Calabar teaching Hospital, South Nigeria [28], Iran 47.5% [29], China 43.1% [30], Brazil 46.7% [31], France 47% [21], Southern US 40% [32], John Hopkins Medical Institution USA 56% [33], another study in USA 46.1% [16] and Taiwan 27.4% [34]. These discrepancies might be due to various factors including differences in the geographical area, socio-cultural variation, characteristics of study participants and the inclusion and exclusion criteria used.…”
Section: Discussioncontrasting
confidence: 76%
“…This network of specific physiological pathways is the primary determinant of neuropathology to have a direct impact on health including sleep. The finding of this study coincides with a study done in Nigeria [19,20] and Mexico [26].…”
Section: Discussionsupporting
confidence: 92%
“…Similarly, studies conducted in Nigeria among HIVpositive outpatients reported that 46.2% in University of Calabar Teaching Hospital and 59.3% in Lagos State University Teaching Hospital had sleep disorders and poor sleep quality respectively. Elevated systolic blood pressure, shorter duration of HIV diagnosis and highly active antiretroviral therapy (HAART) type were associated with sleep disorders and poor sleep quality (Bisong 2017;Oshinaike et al 2014).…”
Section: Introductionmentioning
confidence: 99%